Facile One-Pot Multicomponent Synthesis of Pyrazolo-Thiazole Substituted Pyridines with Potential Anti-Proliferative Activity: Synthesis, In Vitro and In Silico Studies - Islam H. El Azab; Rania B. Bakr; Nadia A. A. Elkanzi (Molecules, 2021)
Pyrazolothiazole-substituted pyridine conjugates are an important class of heterocyclic compounds with an extensive variety of potential applications in the medicinal and pharmacological arenas. Therefore, herein, we describe an efficient and facile approach for the synthesis of novel pyrazolo-thiazolo-pyridine conjugate 4, via multicomponent condensation. The latter compound was utilized as a base for the synthesis of two series of 15 novel pyrazolothiazole-based pyridine conjugates (5–16). The newly synthesized compounds were fully characterized using several spectroscopic methods (IR, NMR and MS) and elemental analyses. The anti-proliferative impact of the new synthesized compounds 5–13 and 16 was in vitro appraised towards three human cancer cell lines: human cervix (HeLa), human lung (NCI-H460) and human prostate (PC-3). Our outcomes regarding the anti-proliferative activities disclosed that all the tested compounds exhibited cytotoxic potential towards all the tested cell lines with IC50 = 17.50–61.05 µM, especially the naphthyridine derivative 7, which exhibited the most cytotoxic potential towards the tested cell lines (IC50 = 14.62–17.50 µM) compared with the etoposide (IC50 = 13.34–17.15 µM). Moreover, an in silico docking simulation study was performed on the newly prepared compounds within topoisomerase II (3QX3), to suggest the binding mode of these compounds as anticancer candidates. The in silico docking results indicate that compound 7 was a promising lead anticancer compound which possesses high binding affinity toward topoisomerase II (3QX3) protein.